Simplicial embeddings between multicurve graphs - Erlandsson, Viveka; Fanoni, Federica (Michigan mathematical journal, 2017)
We study some graphs associated to a surface, called kmulticurve graphs, which interpolate between the curve complex and the pants graph. Our main result is that, under certain conditions, simplicial embeddings between multicurve graphs are induced by π1-injective embeddings of the corresponding surfaces. We also prove the rigidity of the multicurve graphs.
Gesehen am 16.03.2018